Housing and Feeding Management Practices Followed by Goat Keepers of Middle Gujarat - Jegoda, Mahendra N; Modi, Rakesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was conducted in selected areas of Dahod and Kheda districts of Middle Gujarat to ascertain the housing and feeding management practices followed by goat keepers. The data was collected from randomly selected 240 goat keepers (120 each from Dahod and Kheda district) through personal interview with the help of pre-tested structured schedule. The present study revealed that majority of the goat keepers (65.83%) had an enclosed shed for housing their goats followed by open shelter during day or night time by using a deshi clay tiles (61.25%) and thatched type roofed materials (26.67%) and 97.50 % of the goat keepers housed their goats on kutcha floor attached to human dwelling (56.67%) and near to human dwelling (42.50%). Majority of goat keepers (88.75%) used wooden pole in goat shelter and 93.33 % of the goat keepers regularly cleaned goat shelter. Only two fifth of the respondents (40.0%) used feeding trough in goat shelter. Majority of the goat keepers (74.17%) maintained the goats under extensive system followed by semi-stall-feeding system (25.83%) by allowing 4-6 hours of browsing time per day (70.0%) on fallow land or/and forest pasture area by covering about 3-4 km distances daily by flock. About 46.67% goat keepers provided green fodder regularly, while 54.17% respondents fed locally available tree leaves and loppings to the goats regularly and 75.42 % offered dry forages occasionally to goats as per availability of browse, while more than half (57.92 %) of the goat keepers fed home-made concentrates/grains mixture to lactating goats and 64.17 % of the goat keepers provided tube well water for drinking to goats. The district-wise differences were more in providing roofing materials, feeding trough and source of drinking water, and the grazing land was more of plain type in Kheda district.